(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
This research aims to examine the role of time-directed resource consumption accounting (TD-RCA) techniques in achieving competitive advantage for economic units by improving costing accuracy, rationalizing resource consumption, and enhancing product quality. TD-RCA relies on analyzing resource consumption based on the actual time of activities, which helps determine the fair cost of products, reduce waste, and achieve higher operational efficiency. Process reengineering also contributes to the redesign of manufacturing activities with the aim of eliminating unnecessary processes and enhancing customer value, leading to reduced costs and improved product quality. The research focuses on the application of these two techniques in a ready-made garment factory in Najaf. The results showed that combining the two techniques helps reduce overall costs, increase the factory’s competitiveness, and enhance its responsiveness to market demands. The research recommends the adoption of these modern techniques in cost management, given their positive impact on achieving a sustainable competitive advantage, achieving optimal resource utilization, and enhancing production efficiency.